2006
DOI: 10.1110/ps.062328306
|View full text |Cite
|
Sign up to set email alerts
|

The structure of GDP‐4‐keto‐6‐deoxy‐d‐mannose‐3‐dehydratase: A unique coenzyme B6‐dependent enzyme

Abstract: L-Colitose is a 3,6-dideoxysugar found in the O-antigens of some Gram-negative bacteria such as Escherichia coli and in marine bacteria such as Pseudoalteromonas tetraodonis. The focus of this investigation, GDP-4-keto-6-deoxy-D-mannose-3-dehydratase, catalyzes the third step in colitose production, which is the removal of the hydroxyl group at C39 of GDP-4-keto-6-deoxymannose. It is an especially intriguing PLP-dependent enzyme in that it acts as both a transaminase and a dehydratase. Here we present the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 28 publications
(39 reference statements)
3
67
0
Order By: Relevance
“…In many examples, the PLP cofactor is involved in transamination reactions, which typically begin when glutamate or another amino donor reacts with the internal aldimine. A transient geminal diamine is first formed (Scheme 2), which subsequently collapses to form a Schiff base between the cofactor and glutamate, referred to as the external aldimine.A possible dehydration reaction mechanism for ColD, based on both biochemical and structural data, is presented in Scheme 3 (13,18). Consistent with all presently available data, it is thought that after the PLP has been converted to PMP, a Schiff base is then formed between the sugar C4′ and the PMP cofactor that is noncovalently bound to ColD.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In many examples, the PLP cofactor is involved in transamination reactions, which typically begin when glutamate or another amino donor reacts with the internal aldimine. A transient geminal diamine is first formed (Scheme 2), which subsequently collapses to form a Schiff base between the cofactor and glutamate, referred to as the external aldimine.A possible dehydration reaction mechanism for ColD, based on both biochemical and structural data, is presented in Scheme 3 (13,18). Consistent with all presently available data, it is thought that after the PLP has been converted to PMP, a Schiff base is then formed between the sugar C4′ and the PMP cofactor that is noncovalently bound to ColD.…”
supporting
confidence: 53%
“…Instead, ColD contains a histidine residue (His 188) at the homologous position, which does not form a covalent bond with the cofactor. Interestingly, the ColD active site is markedly devoid of potential catalytic bases other than His 188, suggesting that this residue functions as the sole proton donor/ acceptor in the catalytic mechanism (13). It is also noteworthy that ColD catalyzes the reaction using only PLP.…”
mentioning
confidence: 99%
“…, determined by the ProtParam tool from the Expasy Proteomics Server). The wild-type enzyme required for functional studies was expressed and purified as previously reported (3).…”
Section: Methodsmentioning
confidence: 99%
“…Crystallization of H188N ColD-Crystallization conditions were first surveyed by the hanging drop method of vapor diffusion using a sparse matrix screen developed in the laboratory. Large single crystals were subsequently grown via batch methods as previously described (3). The concentrations of the protein solutions were typically 25 mg/ml, and they contained 25 mM Tris (pH 8.0) and 100 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation